Review of the subgenus Turcmenicola Bogatchev, 1952, the genus Colposcelis Dejean, 1834 (Coleoptera: Tenebrionidae: Tentyriini) - Bekchanov, Norbek Kh.; Nabozhenko, Maxim V.; Bekchanova, Mokhira Kh. (Zootaxa, 2023)
The subgenus Turcmenicola Bogatchev, 1952 (genus Colposcelis Dejean, 1834) is reviewed. Representatives of the studied taxon occur in the most lifeless rocky, gravelly and clayey areas of the deserts of Middle Asia (Ustyurt plateau, Kyzylkum desert, foothills of southern Kugitang, Betpak-Dala desert). Turcmenicola comprises five species from which two are described here as new: C. ustyurtensis Bekchanov & Nabozhenko sp. n. (Uzbekistan, Karakalpakstan, eastern part of Ustyurt plateau) and C. khudaybergani Bekchanov, Nabozhenko & Bekchanova, sp. n. (Uzbekistan, Karakalpakstan, Amudarya and Beruni districts). The following new synonymy is proposed: Colposcelis jachontovi (Bogatchev, 1952) = Colposcelis kerzhneri Medvedev, 1970, syn. n. A key to species of Turcmenicola is given.